Fixed-Term Homotopy. (13th February 2013) - Vazquez-Leal, Hector; Khan, Yasir; Filobello-Nino, Uriel; Sarmiento-Reyes, Arturo; Diaz-Sanchez, Alejandro; Cisneros-Sinencio, Luis-F.
Abstract : A new tool for the solution of nonlinear differential equations is presented. The Fixed-Term Homotopy (FTH) delivers a high precision representation of the nonlinear differential equation using only a few linear algebraic terms. In addition to this tool, a procedure based on Laplace-Padé to deal with the truncate power series resulting from the FTH method is also proposed. In order to assess the benefits of this proposal, two nonlinear problems are solved and compared against other semianalytic methods. The obtained results show that FTH is a power tool capable of generating highly accurate solutions compared with other methods of literature.